2015
DOI: 10.1088/2043-6262/6/3/035015
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of gold nanoparticles by microwave heating and application of spectroscopy to study conjugate of gold nanoparticles with antibody E. coli O157:H7

Abstract: Gold nanoparticles (AuNPs) of 15-20 nm size range have attracted attention for producing smart sensing devices as diagnostic tools in biomedical sciences. Citrate capped AuNPs are negatively charged, which can be exploited for electrostatic interactions with some positively charged biomolecules like antibodies. In this paper we describe a method for the low cost synthesis of gold nanoparticles using sodium citrate (Na 3 Ct) reduction in chloroauric acid (HAuCl 4 .3H 2 O) by microwave heating (diameter about 13… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 26 publications
2
24
0
Order By: Relevance
“…Wang and Alocilja recently demonstrated a rapid and sensitive method for bacterial detection reaching a sensitivity of 10 CFU/mL with a linear range of 10 1 –10 6 CFU/mL for E. coli O157:H7 [ 25 ]. They used polymer-coated magnetic nanoparticles to first extract E. coli O157:H and then performed a sandwich assay for electrochemical readout of Au nanoparticles targeted to the extracted E. coli , which could be completed within 1 h. Ngo et al (2015) also attempted labeling for transmission electron microscopy, UV-Vis spectroscopy and FTIR of E. coli O157:H7 with Au nanoparticles (12–14 nm diameter) stabilized by thiol surfactant (3-mercaptopropionic) and directly conjugated with anti- E. coli O157:H7 antibodies [ 26 ]. An additional report on the detection of E. coli 0157:H7 in urine sample used Au NPs conjugated with cysteine and unspecific electrostatic adhesion to E. coli [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Wang and Alocilja recently demonstrated a rapid and sensitive method for bacterial detection reaching a sensitivity of 10 CFU/mL with a linear range of 10 1 –10 6 CFU/mL for E. coli O157:H7 [ 25 ]. They used polymer-coated magnetic nanoparticles to first extract E. coli O157:H and then performed a sandwich assay for electrochemical readout of Au nanoparticles targeted to the extracted E. coli , which could be completed within 1 h. Ngo et al (2015) also attempted labeling for transmission electron microscopy, UV-Vis spectroscopy and FTIR of E. coli O157:H7 with Au nanoparticles (12–14 nm diameter) stabilized by thiol surfactant (3-mercaptopropionic) and directly conjugated with anti- E. coli O157:H7 antibodies [ 26 ]. An additional report on the detection of E. coli 0157:H7 in urine sample used Au NPs conjugated with cysteine and unspecific electrostatic adhesion to E. coli [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results yielded highly stable AuNPs with diameters of ~4.0 nm and ~1.0 nm depending on the MW irradiation time (40 s and 70 s, respectively_. Similarly, Thanh Ngo et al [85] made use of MW heating for the synthesis of antibody functionalized AuNPs (13–15 nm in diameter) with antibacterial activity. HAuCl 4 and Na 3 Ct were used as precursors for the synthesis of the AuNPs, which were posteriorly functionalized with an antibody against E. coli O157:H7, using N -hydroxy succinimide (NHS) and carbodimide hydrochloride (EDC) coupling chemistry.…”
Section: Microwave Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…[4][5][6][7][8][9] In order for high yield synthesis of Au-NPs with well-defined shape and size, the Turkevich method has been extensively modified such as by changing the addition order of the reactants, using different reducing agents, adjusting the ratio of HAuCl4 to sodium citrate and pH values as well as adding new stabilisers. [10][11][12][13][14][15][16][17][18] Replacement of water by its expensive isotope, deuterium oxide, was shown to produce smaller sizes of Au NPs (5.3 ± 1.1 nm), compared with the particles (9.0 ± 1.2 nm) produced in pure water which was attributed to faster reduction of precursor. 19 An increase in reaction rate was observed by reversing the order of the reactants' addition (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…2,7-dihydroxy naphthalene as the reducing agent and cetyltrimethyl ammonium bromide as the stabilizer). 16,[24][25][26][27] These studies generally used domestic multimode microwave systems (600-1000 W) and their results revealed that microwave assisted fast temperature ramping was highly effective to synthesize Au-NPs (e.g. 20.01 (±2.05) nm or 12.04 (±1.35) nm).…”
Section: Introductionmentioning
confidence: 99%